Klima, Corona und das Christentum: Religiöse Bildung für nachhaltige Entwicklung in einer verwundeten Welt - Gärtner, Claudia (transcript, 2020)
Political theology meets critical educational theory: guidelines and practical elements for political religious education for sustainable development.